INFLUENCE OF FORMULATED DIETS WITH VARYING PROTEIN LEVELS ON GROWTH AND AMMONIA EXCRETION IN THE FRY OF INDIAN MAJOR CARP, CIRRHINA MRIGALA - Mathivanan, R. (Journal of Indian Fisheries Association, 2006)
The influence of formulated isocaloric diets of different protein levels (30, 35, 40,45 and 50o/o) on the growth and ammonia excretion of the Indian major carp·Cirrhina mrigala fry was studied for a rearing period of four weeks in the laboratory. Fishmeal, groundnut oilcake and silkworm pupae formed the source of protein in all the diets. As the dietary protein level increased from 30 to 40o/o, the growth and conversion efficiency increased significantly. Further increase in the protein level resulted in decrease in growth and conversion efficiency. Growth rate, weight gain (0/o ), and gross and net feed conversion efficiencies were maximum at 40%) dietary protein level. Ammonia excretion was directly proportional to the level of protein in the diet. Keywords : Cirrhina mrigala, formulated diet, ammonia, dietary protein